Audio-visual Media and Flyers to Reduce the Anxiety of Elementary School Students in Dealing with Menarche - Anis Nur Laili; Moh. Choirin (Health Notions, 2018)
Menarche is a special feature before maturity in a woman. The main problem that often arises when teenagers experience menarche is unpreparedness in facing these reproductive changes. This study aims to analyze the effect of the use of audio-visual and flyer media in order to reduce adolescent anxiety in dealing with menarche. The design of this experimental quasy study was a pre-test and post-test. The number of respondents involved in the study was 27 students of elementary school. The independent variables studied were the use of audio-visual media and flyers in health education about menarche; while the dependent variable was the level of anxiety in dealing with menarche. Data about the level of anxiety was collected through filling in the questionnaire, then analyzed using the T test. The results of data analysis showed a difference in the level of adolescent anxiety between before and after the intervention, with p-value = 0.000. Audio visual media could clarify a problem and its handling, through an interactive learning process, the diversity of learning activities could be improved. Media flyers could provide complete and detailed information, even about things that were not given orally. This media was designed simply in accordance with the ability of elementary school students. Educators should use audio visual and flyers, especially audio visuals, in order to provide knowledge about menarche, so that female students are better prepared to face menarche. Keywords: Menarche, Health education, Audio-visual, Fliyer, Anxiety